A comparison of breast feeding practices among urban and rural areas of Rangareddy district of Telangana - Kumar, M. Vijay; Acharya, Indranil; Acharya, Jayanti P.; Shravani, Puligila Raj; Ramya, Sabbineni (International Journal Of Community Medicine And Public Health, 2017)
Background: Breastfeeding is the normal way of providing young infants with the nutrients they need for healthy growth and development. Methods: A community based cross sectional study was conducted among 800 mothers from urban and rural areas of Rangareddy District. A pre designed pre tested questionnaire was used to interview the mothers. Questionnaire contained questions related to demographic factors and breast feeding practices. Institutional Ethical clearance was taken. Results: The overall prevalence of exclusive breast feeding was 65%, being comparatively more in rural area (68%) which was statistically significant. Colostrum was discarded by 15% mothers in urban and 9% in rural area. Breast feeding was initiated within 1 hour in 184 (46%) in urban area and in 148 (37%) in rural area. Conclusions: Though mothers from rural area had certain favorable breast feeding practices such as demand feeding, colostrum being given but still various inappropriate practices were prevalent in both rural and urban areas.